2012
DOI: 10.4149/av_2011_04_327
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of sweet potato leaf curl virus (SPLCV) isolates from Korea: phylogenetic relationship and recombination analysis

Abstract: Summary. -The complete DNA genome of sweet potato leaf curl virus (SPLCV) from samples obtained from eight regions was amplified by PCR and characterized in this study. The DNA genome of one group (SPLCV Korea group 1) consisted of 2828 nucleotides and that of the second group (SPLCV Korea group 2) consisted of 2829 nucleotides. Sequence comparisons showed that the genome sequences of SPLCV Korea isolates were closely related to those of SPLCV Brazil isolates (FJ969834, FJ969835, and FJ969836), SPLCV Japan iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Detection of SPLCV in vegetative tissues of sweet potatoes with symptoms A PCR detection system was set up with DNA isolated from the leaves of healthy and SPLCV-infected sweet potato plants as reported previously (Park et al, 2010;Choi et al, 2012). Ten plants each from eight cultivars showing typical leaf curl disease symptoms were tested by PCR and 8-10 plants per cultivar showed SPLCV-specific amplification ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of SPLCV in vegetative tissues of sweet potatoes with symptoms A PCR detection system was set up with DNA isolated from the leaves of healthy and SPLCV-infected sweet potato plants as reported previously (Park et al, 2010;Choi et al, 2012). Ten plants each from eight cultivars showing typical leaf curl disease symptoms were tested by PCR and 8-10 plants per cultivar showed SPLCV-specific amplification ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The SPLCV monopartite genome has two open reading frames (ORF) (V1 and V2) in the virion sense and four ORFs (C1, C2, C3 and C4) in the complementary sense, separated by an intergenic region (IR) containing a conserved stem-loop motif, in a 2Á8-kb single-stranded circular DNA (Lotrakul & Valverde, 1999). Complete genome sequences of SPLCV isolates in Korea have been characterized, and their phylogenetic relationships with other sweepovirus species have been determined (Park et al, 2010;Choi et al, 2012). SPLCV and related sweepoviruses have been found in many countries, including Brazil, China, India, Italy, Kenya, Korea, Peru, Spain and Uganda (Banks et al, 1999;Briddon et al, 2006;Kwak et al, 2006;Luan et al, 2006;Miano et al, 2006;Prasanth & Hegde, 2008;Lozano et al, 2009;Paprotka et al, 2010;Albuquerque et al, 2011;Wasswa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sweepoviruses have been reported in many countries including Peru, Italy, Spain, China, Korea, Kenya, Uganda, India, and Brazil [ 1 , 4 , 21 29 ]. Complete genome sequences of SPLCV isolates in Korea have been characterized, and their phylogenetic relationships with other Sweepovirus species have been determined [ 30 , 31 ]. Moreover, complete genome information of Sweepovirus is the most plentiful virus species among all sweet potato-infecting viruses [ 28 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that SPLCV can be transmitted via seed ( Kim et al, 2015 ). Korean isolates of SPLCV were characterized and their full genome sequences were analyzed ( Choi et al, 2012 ; Park et al, 2011 ). Recently, Sweet potato golden vein associated virus was characterized and reported ( Kil et al, 2014 ).…”
mentioning
confidence: 99%